2001
DOI: 10.1080/09540120120063296
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic characteristics and HIV risk behaviour patterns of male sex workers in Madrid, Spain

Abstract: This paper describes the sociodemographic and work characteristics, prevalence of HIV infection and associated risk behaviours among male sex workers (MSWs) in Madrid (Spain). Using an anonymous semi-structured questionnaire, educators attached to a mobile unit under a street-based prostitution programme surveyed 84 MSWs from several Madrid areas. Of the total surveyed: 35% were immigrants, mean age was 23 years, mean period in prostitution was four years; 21% had no primary education; 16% had injected drugs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 14 publications
0
39
1
2
Order By: Relevance
“…In Spain, HIV seroprevalence seems to be very high in this group, both those who admitted intravenous drug use (60%) and those who denied it (17%) [Belza et al, 2001]. The 23.3% rate found among immigrant Ecuatorian transsexuals is high, considering that none of them admitted intravenous drug use.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, HIV seroprevalence seems to be very high in this group, both those who admitted intravenous drug use (60%) and those who denied it (17%) [Belza et al, 2001]. The 23.3% rate found among immigrant Ecuatorian transsexuals is high, considering that none of them admitted intravenous drug use.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population of men engaged in sex work, HIV infection rates range from 10% to 19.8% [7]. Other Spanish research focusing on drug-using MSW who work on the street found that 60% of participants were infected with HIV [6]; however, this research did not provide any information on men engaged in sex work in other venues such as apartments.…”
mentioning
confidence: 95%
“…Some studies indicate that MSW undertake behaviors that place themselves and their regular and occasional partners at risk for HIV infection [2,6,[11][12][13]; however, many also indicate that certain high-risk behaviors are performed less frequently than previously assumed [14]. There is very little research examining such specific risk behaviors among MSW [12,14].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…A number of studies have shown delay of onset of sexual initiation (e.g., Coyle, Kirby, Marin, Gómez, & Gregorish, 2004), whereas other programs have led to significant increases in condom use in populations including heterosexually active individuals (see Johnson, Carey, Marsh, Levin, & Scott-Sheldon, 2003;Neumann et al, 2002, for reviews). However, most of these interventions have been implemented in small-group (e.g., Belza et al, 2001), school (e.g., Blake et al, 2003;Gallant & Maticka-Tyndale, 2004), or individuallevel clinical settings (e.g., Morrison-Beedy & Lewis, 2001). Mass media campaigns, such as televised public service announcement (PSA) campaigns, have recently been shown to be highly effective in changing a variety of behaviors (Hornik, 2002;Noar, 2006) 2001).…”
mentioning
confidence: 99%